Champions of a Free Society: Ideas of Capitalism's Philosophers and Economists - Younkins, Edward Wayne (Lexington Books, 2008)
This book is constructed around great thinkers of the past and present who have been influential in developing the philosophy of freedom. Its main purpose is to provide a survey and overview of the ideas of leading individual philosophers and economists of capitalism who have contributed to developing what might be called the classical liberal or libertarian worldview. Champions of a Free Society endeavors to provide a guide to political and economic thinking about the desirability and construction of a free society that is intelligible to the educated layperson. Edward Younkins provides an historical perspective of the pursuit of political and economic truth. The goal of this book is to present the development of ideas in language that permits generally educated readers to understand and appreciate their significance. The book's chronological approach considers the thinkers and their ideas as they have developed over the course of time. There is much unfulfilled illuminative potential to be found in the ideas of the past and Younkins successfully integrates the ideas of past and current thinkers into a logical contemporary worldview.